Strengthening Branding and Brand Loyalty as a Strategy to Enhance MSME Competitiveness in the Digital Era - Rahmatia Golonggomo; Nida Hasanati; Djudiyah Djudiyah (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
The digital era requires Micro, Small, and Medium Enterprises (MSMEs) to possess high competitiveness through marketing strategies based on brand identity and customer loyalty. From a psychological perspective, branding is not merely a marketing instrument but a symbolic medium through which consumers form emotional attachment, personal identity, and social belonging to a brand. This community service activity aims to improve the understanding and awareness of MSME actors in Gorontalo Regency regarding the importance of branding and brand loyalty in maintaining business sustainability in the digital market. The activities were conducted through interactive training, practical mentoring, and simulations of emotionally driven digital branding strategies, including storytelling, strengthening visual identity, and consistent social media management. The results showed significant improvement in MSMEs’ understanding of brand identity, their ability to create meaningful digital content, and increased interaction with consumers on digital platforms. MSMEs began recognizing the unique characteristics of their brands and understanding that customer loyalty directly influences sales growth and business sustainability. This activity confirms that strengthening branding and brand loyalty not only increases digital visibility but also fosters emotional and psychological bonds between brands and consumers.